2018
DOI: 10.1007/s11099-018-0831-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil Cu contamination destroys the photosynthetic systems and hampers the growth of green vegetables

Abstract: Soil metal contamination leads to a decrease in a yield of crops and is a threat to human health. In the present study, the properties (i.e., photosynthetic pigments, gas-exchange parameters, chlorophyll fluorescence, biomass, leaf area, leaf mass per area) of three green vegetables (i.e., Brassica chinensis, Chrysanthemum coronarium, Brassica alboglabra) grown under various Cu treatments [0, 200, 400, and 600 mg(Cu) kg -1 ] were measured and analysed. The results showed that soil Cu contamination resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
5
16
0
Order By: Relevance
“…Chronic exposure to pollutants and xenobiotics in comparison with the acute treatment significantly affects the level changes of electron transport, i.e., chlorophyll fluorescence parameters. This conclusion was confirmed in our experiments and is in line with [ 60 ], when the stress response is influenced by the duration of exposure to the stressor, but also depending on the concentration and developmental stage, when juvenile plants are usually more sensitive than older plants. Usually, the higher the strength of the stressor, the more the appropriate response of the plant increases.…”
Section: Resultssupporting
confidence: 92%
“…Chronic exposure to pollutants and xenobiotics in comparison with the acute treatment significantly affects the level changes of electron transport, i.e., chlorophyll fluorescence parameters. This conclusion was confirmed in our experiments and is in line with [ 60 ], when the stress response is influenced by the duration of exposure to the stressor, but also depending on the concentration and developmental stage, when juvenile plants are usually more sensitive than older plants. Usually, the higher the strength of the stressor, the more the appropriate response of the plant increases.…”
Section: Resultssupporting
confidence: 92%
“…Sagardoy et al (2010) reported the main limitation to photosynthesis rate in sugar beet was likely due to the reduction of Gs under Zn stress. Lin and Jin (2018) found similar results in an experiment with three vegetables (B. chinensis, C. coronarium, and B. alboglabra) under Cu stress. However, Velikova et al (2011) studied the impact of Ni on the photosynthesis of Populus nigra and found the limitation to photosynthesis rates of this species resulted from the restriction in Gm, not in Gs.…”
Section: Introductionsupporting
confidence: 70%
“…2014). Copper pollution reduces pigment content and inhibits photosynthesis, resulting in reduced plant biomass (Lin & Jin 2018). Faseela et al .…”
Section: Introductionmentioning
confidence: 99%